A Study of Surgical Outcome of Supratentorial Meningioma (Bangladesh Journal of Neuroscience, 2015)
This was descriptive study. This study was carried out at the Department of Neurosurgery Bangabandhu Sheikh Mujib Medical University from April 2010 to April 2014. We have studied 35 cases. After collecting patients admission data, a brief history and clinical examination was done. Supratentorial meningioma was diagnosed primarily by contrast CT scan and MRI of brain which was confirmed by surgery & histopathological examination. After surgery close follow up were done. Most of the sufferer were female 19(54%). The commonest age group was 40-59 years (37.14%). The commonest site of tumors were frontal convexity8(22.9%) and the commonest histological types were meningotheliomatous 12 (34.3%). All of the patients were undergone surgery. Majority of patients were improved after treatment 31(88.6%).Bangladesh Journal of Neuroscience 2015; Vol. 31 (1): 15-20